The World almanac and book of facts 2005. - 4 0 16; 5 (New York, N.Y. : World Almanac Books,;Distributed to the Book trade by St. Martin's Press, 2005)
The World Almanac is the most useful reference book known to modern man.--Internet.
Includes indexes.
Keywords: 2 -- 0; 6; Almanacs, American.;Statistics;Almanacs. -- 20 -- Periodicals; United States -- 20 -- Statistics; 2